Alkali-silica reactivity of lightweight aggregate: A brief overview. (8th February 2021) - Mo, Kim Hung; Ling, Tung-Chai; Tan, Tee How; Leong, Geok Wen; Yuen, Choon Wah; Shah, Syed Nasir
Highlights: Alkali-silica reactivity of lightweight aggregate is reviewed. Expanded clay and shale are non-reactive and can be utilized to reduce ASR. Expanded glass and perlite could exhibit certain degree of reactivity, although not deleterious. Abstract: The alkali-silica reaction (ASR) phenomenon is one of the most severe conditions which could deteriorate concrete. While extensive studies have been done on the reactivity of normal weight aggregate, the ASR mechanism related to the use of lightweight aggregate is not well understood. The paper reviews published findings with regards to the reactivity of lightweight aggregate. The beneficial effect of internal voids within the aggregate to accommodate reaction product seems to be shared by most of the studied lightweight aggregates. However, different types of lightweight aggregate were found to have differing behaviour with regards to ASR. Clay-based lightweight aggregates such as expanded clay and shale are reported to be non-reactive and can be utilized to reduce expansions in concrete experiencing ASR whereas highly siliceous aggregates such as expanded glass and perlite could exhibit certain degree of reactivity, though in most cases it was not deleterious. Further investigations are nevertheless required, especially to fully understand the ASR mechanism in various other types of lightweight aggregate.